G‐Quadruplex‐Based Photooxidase Driven by Visible Light. Issue 1 (13th October 2019) - Gao, Longlong; Tong, Xingyu; Ye, Ting; Gao, Heng; Zhang, Qingqing; Yan, Chenxiao; Yu, Yali; Fei, Yifan; Zhou, Xiaoshun; Shao, Yong
Abstract: The G‐quadruplex (G4)/hemin entity has been widely used as a peroxidase‐mimic DNAzyme to catalyze the substrate oxidation with exogenous and concentrated H2 O2 as oxidant for developing various devices. Herein, a G4‐based oxidase‐mimic DNAzyme that can be driven by visible light was developed. The oxidant is in situ produced by light irradiation. As a natural photosensitizer, Hypericin (Hyp) alone in solution is inactive because of aggregation. However, the binding with G4 triggers the fluorescence emission and activates Hyp to produce singlet oxygen ( 1 O2 ) by energy transfer to the dissolved oxygen. Therefore, the G4/Hyp entity can serve as a photooxidase via the 1 O2 pathway to catalyze the substrate oxidation. Since the G4‐bound Hyp can be excited by almost the whole range of visible light, the photooxidase should cover a wide range of photocatalytic applications. Similar to the peroxidase‐mimic DNAzyme, the G4 sequence can regulate the photooxidase activity and metal ions can serve as efficient cofactors to activate the photooxidase capacity for an inactive G4 structure. This work provides an alternative to build a versatile G4‐based photooxidase with straightforward tunability of its activity. Abstract : G‐quadruplex (G4) with an appropriate conformation binds a photosensitizer of hypericin (Hyp) to serve as a G4‐based photooxidase. Different from G4/hemin peroxidase, the photooxidase works without exogenous oxidant addition. The G4‐Hyp photooxidase can be activated by almost the whole range of visible lights to in situ produce singlet oxygen for substrate oxidation.